Port service quality in the supply chain management context - Poh, Patricia Xiang Qi. (2012)
The port industry is a specialised industry and is usually the gateway to many markets involving sea transport. However, there has been a general shift in the roles of the port. Besides the traditional function of being the facilitator, providing of infrastructure and equipment, contemporary ports have now been integrated into supply chains. This essentially means that ports are now considered as only an element in a supply chain, instead of a standalone entity. Hence, the standard of performance by the ports has a bearing effect on the rest of the supply chain.